THE EFFECT OF FASHION LIFESTYLE AND PRODUCT KNOWLEDGE ON THE PURCHASE INTEREST OF BATIK SPERO JOSS - Ambarwati, Agniz Ruri; Ayuning Pertiwi, Fia (LPPM STAI Muhammadiyah Probolinggo, 2023)
Spero joss batik fashion lifestyle is one of the popular batik uniforms in Probolinggo City. Spero Joss Batik is a development of batik using jumputan and stamping techniques. This research aims to determine the influence of fashion lifestyle and product knowledge on buying interest in Spero Joss batik. This research is quantitative in nature, with sample selection using a non-probability sampling method, specifically purposive sampling with a total of 100 respondents. Data analysis was carried out through a combination of descriptive analysis and multiple linear regression. Data was collected through the use of a questionnaire. This research was conducted at SMP Negeri 2 Probolinggo City. Based on the data obtained, lifestyle hypothesis testing has a significant effect on buying interest and product knowledge also has a significant influence on buying interest in Spero Joss batik. From the results of this research, it is hoped that Spero Joss Batik can be better known by students in Probolinggo City by using it as a role model for making batik uniforms with their own work, in order to maintain Indonesia's cultural heritage.